2018
DOI: 10.3892/ol.2018.8061
|View full text |Cite|
|
Sign up to set email alerts
|

Downregulation of ubiquitin-specific peptidase 39 suppresses the proliferation and induces the apoptosis of human colorectal cancer cells

Abstract: Ubiquitin-specific peptidase 39 (USP39) has been reported to participate in the mitotic spindle checkpoint and the process of cytokinesis. and has been identified as a therapeutic target for various types of cancer. However, the effect of USP39 in colorectal cancer (CRC) has not been investigated. To explore the functional role of USP39 in CRC cell growth, lentivirus-mediated RNA interference was applied to inhibit USP39 expression in SW1116 and HCT116 cells. The relative USP39 mRNA and protein expression leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Thus, this deubiquitinase may not act as an actual deubiquitinase. Several studies reported that USP39 may act as an oncogenic factor in several cancers, such as breast cancer, thyroid carcinoma, and hepatocellular carcinoma (24)(25)(26)(27), and they revealed a novel role for USP39-mediated mRNA splicing in the process of cell proliferation (28). However, it is less clear whether or how USP39 plays a role in other biological functions, such as antiviral immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this deubiquitinase may not act as an actual deubiquitinase. Several studies reported that USP39 may act as an oncogenic factor in several cancers, such as breast cancer, thyroid carcinoma, and hepatocellular carcinoma (24)(25)(26)(27), and they revealed a novel role for USP39-mediated mRNA splicing in the process of cell proliferation (28). However, it is less clear whether or how USP39 plays a role in other biological functions, such as antiviral immunity.…”
Section: Discussionmentioning
confidence: 99%
“…USP39 is also reported to be a pivotal regulator of EGFR pre-mRNA splicing [10]. In addition, an oncogenic role for USP39 has been reported in many malignant tumors, such as prostate cancer [10], oral squamous cell carcinoma [11], gastric cancer [12], melanoma [13], osteosarcoma [14], breast cancer [15], hepatocellular carcinoma [16], medullary thyroid carcinoma [17], lung cancer [18], pancreatic cancer [19], colorectal cancer [20], and renal cell carcinoma [21]. However, the role of USP39 in glioma has not been well defined.…”
Section: Introductionmentioning
confidence: 99%
“…USP39 is essential for mitotic spindle checkpoint integrity and controls mRNA levels of Aurora B [4]. Down-regulation of USP39 suppresses the proliferation and induces the apoptosis of human colorectal cancer cells [21]. Knockdown of USP39 inhibited the growth of osteosarcoma cells and induced apoptosis in vitro [22].…”
Section: Discussionmentioning
confidence: 99%